Nurses and the aging problem - Pęgiel-Kamrat, Jolanta; Malicka-Kaczmarzyk, Ewa; Zarzeczna-Baran, Marzena; Wojdak-Haasa, Ewa (Polish Journal of Public Health, 2009)
Introduction. The progressive aging of society is a huge challenge to public health. According to demographic prognosis in 2020 the number of 60-year-olds and over will exceed 20% of the living society. This phenomenon concerns Poland as well. The growing number of patients require social and medical care. A competent nurse should play a vital role in caring for the elderly, adapting resources to individual needs and actual situation.Aim. The paper aims to determine nurses’ knowledge of the senility problem, caring for the elderly patient and different forms of support to the elderly.Material and methods. The study material was collected in the form of a diagnostic poll. The anonymous survey including 39 questions was the research method.Results. The majority of the surveyed (68%) claimed the chief indication of senility to be self- independence restriction and drop of one’s adaptive aptitude (63%). Almost 75% of the surveyed claimed the most frequent problems being cardiovascular disease (78%) and locomotion restriction (77%) to be the major determinants of aging. The crucial problems of the senile is perceived to be solitude (90%) and the feeling of needlessness (80%). According to the questioned (53%) the NFZ (National Health Fund) services do not meet the needs of the senile.Conclusions. The knowledge of nurses about aging and caring process of the elderly is insuffi cient. Caring for the elderly is not performed with respect to physical condition evaluation and individual caring plan.